Effect of geraniol on temporal patterns of clock gene products during endometrial carcinogenesis in rats. Issue 4 (3rd July 2016) - Shanmugapriya, S.; Bhavani, P.; Subramanian, P.
Abstract: The most common cancer in the female genital tract is malignancy of the endometrium ranking fourth among the aggressive cancers that affects women. Biological clock controls the daily modifications of physiological processes, which sequentially regulate numerous functions in the human body. In this study, female Wistar rats were divided into four groups: group I – control, group II – MNNG (N-methyl-N′-nitro-N-nitrosoguanidine-150 mg/kg) given by intravaginal detention of absorbent cottons dipped with 150 mg of MNNG for weekly twice; group III – co-administration of geraniol (MNNG + GOH) (150 mg/kg b.w); group IV – oral administration of GOH only. The expression of protein levels of PER, CRY, BMAL1 and CLOCK at different time points (00:00, 04:00, 08:00, 12:00, 16:00 and 20:00 h) were analyzed over the 24-h period by western blotting. In MNNG-induced group, PER and CRY protein levels were downregulated, whereas BMAL1 and CLOCK expression was upregulated at 00:00 and 20:00. Administration of GOH reversed the expression level of clock gene products observed in MNNG-treated rats. The results indicate that the expression of clock gene products is affected during endometrial carcinogenesis. Earlier reports suggest that carcinogenesis could modify circadian rhythms and our results add additional evidences in similar lines. Our results suggest that anticarcinogenic action of GOH could be via normalizing the expression of clock gene products. The mechanisms for this alteration of clock gene expression are desirable to investigate in future.